All‐trans‐retinoic acid activated mast cells via Mas‐related G‐protein‐coupled receptor‐X2 in retinoid dermatitis. (22nd May 2019) - Zheng, Yi; Che, Delu; Peng, Bin; Hao, Yong; Zhang, Xinyue; He, Langchong; Geng, Songmei
Abstract: Background: Retinoic acid (RA)‐induced dermatitis is the most frequent side‐effect limiting its widespread use. However, the exact mechanisms triggering dermatitis are not fully understood, including the role of skin mast cells. The newly discovered Mas‐related G‐protein‐coupled receptor‐X2 (MRGPRX2) in mast cells mediates pseudoallergic drug reactions in several types of dermatitis. A possible contribution of MRGPRX2 to contact dermatitis induced by RA has hitherto not been examined. Objectives: To investigate whether all‐ trans ‐RA (ATRA) activates mast cells via MRGPRX2/MrgprB2 (the mouse orthologue), contributing to the pathogenesis of retinoid‐induced dermatitis. Methods: Wild‐type (WT) and MrgprB2 −/− mice were treated with topical ATRA to observe local inflammation and mast cell degranulation in vivo by the use of haematoxylin and eosin and immunofluorescence staining. Release of histamine and release of β‐hexosaminidase were measured and calcium influx was detected in Laboratory of Allergic Disease 2 (LAD2) cells with specific knockdown targeting MRGPRX2 by small interfering RNA (siRNA) and in primary cells from MrgprB2 −/− mice. Results: As compared with WT mice, MrgprB2 −/− mice showed resistance to ATRA‐triggered contact dermatitis and local inflammatory reactions in the paws. ATRA activated mast cells via the MrgprB2 pathway in murine cells, and via the MRGPRX2 pathway in human mast cells. Conclusions: ATRA‐induced dermatitis could be achieved by activating mast cells via MRGPRX2/MrgprB2, which may provide a potential therapy target to reduce the side‐effect.